Structure and Dynamics of Mono- vs. Doubly Lipidated Rab5 in Membranes - Münzberg, Eileen (Int J Mol Sci, 2019)
The Rab5 small GTPase is a regulator of endosomal trafficking and vesicle fusion. It possesses two adjacent cysteine residues for post-translational geranylgeranylation at its C-terminus for the protein to associate with the early endosome membrane. We compare the effect of mono-lipidification of only one cysteine residue with the doubly modified, fully functional Rab protein in both guanosine diphosphate (GDP)- and guanosine triphosphate (GTP)-bound states and in different membranes (one, three, and six-component membranes). Molecular simulations show that the mono-geranylgeranylated protein is less strongly associated with the membranes and diffuses faster than the doubly lipidated protein. The geranylgeranyl anchor membrane insertion depth is smaller and the protein–membrane distance distribution is broad and uncharacteristic for the membrane composition. The mono-geranylgeranylated protein reveals an unspecific association with the membrane and an orientation at the membrane that does not allow a nucleotide-specific recruitment of further effector proteins. This work shows that double-lipidification is critical for Rab5 to perform its physiological function and mono-geranylgeranylation renders it membrane-associated but non-functional.